P243 Investigating the mechanisms of repetitive transcranial magnetic stimulation using mouse motor learning paradigms and in vivo 2 photon imaging. Issue 3 (March 2017) - Tang, A.; Bennett, W.; Hadrill, C.; Collins, J.; Wills, K.; Puri, R.; Garry, M.; Hinder, M.; Summers, J.; Rodger, J.; Canty, A.
Abstract : Introduction: Modulation of cortical plasticity with repetitive transcranial magnetic stimulation (rTMS) has become a popular method of neuromodulation in both clinical and non-clinical populations. In particular, complex pattern rTMS such as intermittent theta burst stimulation (iTBS) has been shown to induce long lasting effects. However, the biological mechanisms underpinning rTMS induced plasticity remains poorly understood. Objectives: Rodent models offer the potential to investigate not only the behavioural, but also the structural and molecular mechanisms induced with stimulation. This study examined changes in skilled motor behaviour and structural reorganisation at the synaptic level following iTBS to the motor cortex. Methods and materials: We use a rodent-specific TMS circular coil (8 mm outer diameter) to deliver iTBS (600 pulses) over the motor cortex of awake adult male mice. For motor learning paradigms, C57Bl6/J mice receive daily iTBS or sham immediately prior to ( n = 16 per group) or after ( n = 8 per group) skilled pellet-reaching training for 10 days. In a separate group; Thy1-GFPM mice ( n = 5) underwent cranial window insertion overlying the right motor cortex to enable visualisation of excitatory cortical neurons in the upper layers of the motor cortex. Images of synaptic structures were collected at regular intervals before and after iTBS and analysed for alterations in connectivity resulting from stimulation. Results: Priming iTBS increased skill accuracy by 8.5% ± 3.4 ( p = 0.02) but did not alter the rate of learning ( p = 0.24). Preliminary analysis shows that consolidation iTBS did not alter skill accuracy ( p = 0.25) or the rate of learning ( p = 0.12). A single session of iTBS decreased dendritic spine density at 24 h (−7% p = 0.015) and 48 h (−9% p = 0.001) post-stimulation which returned to baseline levels by 7 days post-stimulation ( p = 0.2). Conclusions: These results show that rTMS induces both behavioural and structural plasticity in the motor cortex. Priming iTBS had a non-homeostatic interaction with motor behaviour whilst iTBS alone transiently decreased dendritic spine density. These result aid in the understanding of rTMS induced plasticity mechanisms which is essential in the optimisation of rTMS to treat neurological disease and disorders.